Вплив прецедентної практики Європейського суду з прав людини на судову практику України: нові можливості - Вишняков, Олександр Костянтинович; Вишняков, Александр Константинович; Vishnjakov, Aleksandr (My University, 2011)
The inadequate growth of amount of appeals before the European Court on Human Rights in regard to some Council of Europe member-states is caused by the so-called «systemic deficiencies» into these states. One of factors that generate them is a deficit of impact of ECHR practice on national judicial practice. Implementation of precedent practice of ECHR by courts is one of ways to overcome this deficit in Ukraine.
Вишняков О. К. Вплив прецедентної практики Європейського суду з прав людини на судову практику України: нові можливості / О. К. Вишняков // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C. 164-170.
Keywords: захист прав людини; системні недоліки; прецедент; судова практика; защита прав человека; системные недостатки; прецедент; судебная практика; protection of human rights; systemic weaknesses; precedent; arbitrage practice